Deformation-induced spatiotemporal fluctuation, evolution and localization of strain fields in a bulk metallic glass. (August 2015) - Wu, Y.; Bei, H.; Wang, Y.L.; Lu, Z.P.; George, E.P.; Gao, Y.F.
Abstract: Deformation behavior and local strain evolutions upon loading and unloading of a bulk metallic glass (BMG) were systematically investigated by in situ digital image correlation (DIC). Distinct fluctuations and irreversible local strains were observed before the onset of macroscopic yielding. Statistical analysis shows that these fluctuations might be related to intrinsic structural heterogeneities, and that the evolution history and characteristics of local strain fields play an important role in the subsequent initiation of shear bands. Effects of sample size, pre-strain, and loading conditions were systematically analyzed in terms of the probability distributions of the resulting local strain fields. It is found that a higher degree of local shear strain heterogeneity corresponds to a more ductile stress–strain curve. Implications of these findings are discussed for the design of new materials. Highlights: Strain heterogeneity and evolution measured by digital image correlation. Microscopic strain heterogeneity correlated with the macroscopic ductile or brittle behavior. Effects of sample size, pre-strain, loading conditions on strain fluctuations are systematically analyzed.